The determinants of financial behavior among young graduates of Universiti Teknologi Mara (UiTM) Segamat, Johor / Nor Syahira Mohd Noor - Mohd Noor, Nor Syahira (Faculty of Business and Management, 2019)
Nowadays, the bankruptcy rate among youth keep increasing whereby it totally gives impact to youth, economy and society. Besides that, youth is the main group that contribute in building up the economy. Bankruptcy is one of the serious issue among youth and usually it is due to weak of personal fmancial management. A healthier financial behavior would lead to a good financial management. A good financial behavior of an individual depends on several factors. Therefore, the purpose of this study to determine the financial behavior among young graduates. There are several independent variables that might influence financial behavior such as personal financial knowledge, peers, parental role modelling and parent's direct teaching. In this research, questionnaire had been distributed to 160 respondents who are graduates from batch March 2019 of Faculty of Business and Management Universiti Teknologi Mara (UiTM) Kampus Segamat,Johor. All the results and feedback from the respondents had been recorded and analysed using SPSS version 20. The finding of this research shows that personal financial knowledge, parental role modelling and parents direct teaching have a significant and positive relationship with the financial behavior. The result from this study may be used to increase a good financial behavior among young graduates.